Screening for salinity tolerance of Oryza glaberrima Steud. seedlings - GANDONOU, GBOSSÈGNON CHRISTOPHE BERNARD; LUTTS, Stanley; PRODJINOTO, Hermann (My University, 2018)
Rice (Oryza sativa) is a salt-sensitive species and improvement of salt resistance is a major goal for plant breeders. Some species of Oryza genus may constitute an interesting source of genes involved in stress resistance for cultivated rice improvement. The African rice Oryza glaberrima is poorly described for its response to salt stress. Twenty-five accessions of O. glaberrima were exposed during 2 weeks to 0 or 60 mM NaCl in nutrient solution. Morphological and physiological parameters were recorded and used to perform principal component analysis allowing us to consider three contrasting groups (saltresistant, medium, and salt-sensitive). Most of the tested lines appeared more salt-sensitive than the moderately salt-resistant cultivar I Kong Pao from O. sativa. Salt-sensitivity index was higher for roots than for shoots and O. glaberrima was poorly efficient for regulation of Na+ translocation from the root to the shoot. Some accessions such as TOG5307 however were able to maintain a high net photosynthesis under salt conditions and exhibited a high level of tolerance to accumulated Na+ ions and a high capacity for osmotic adjustment. It is concluded that these salt-tolerant accessions constitute a promising material for rice improvement through inter-specific crosses with O. sativa.
Keywords: African rice; NaCl; Oryza glaberrima; salinity; salt stress.